Pengaruh Pijat Refleksi Kaki Terhadap Kualitas Tidur Pada Anak Usia 6 – 10 Tahun Di Rumah Sakit Umum Daerah Siti Aisyah Lubuklinggau Tahun 2025 - Erika Qurnia; Tuti Rohani; Murwati Murwati (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Based on 2020 WHO data, approximately 10% to 20% of children worldwide experience sleep problems, as well as health problems caused by sleep deprivation in adolescents, such as obesity and mental disorders. A 2020 study by the National Sleep Foundation (NSF) in the United States found that children under 16, including those aged 6-10, frequently experience sleep deprivation. 60% complained of daytime fatigue, and 15% reported feeling sleepy at school. The results of a systematic review and meta-analysis indicate that 76% of pediatric patients undergoing hospitalization experience poor sleep quality and insufficient sleep duration. Objective: To determine the effect of foot reflexology massage on sleep quality in children aged 6-10 years at Rumah Sakit Umum Daerah Siti Aisyah Lubuklinggau in 2025.The study design was pre-experimental, using a one-group pre-test post-test design, involving one group of subjects. Data were obtained by administering the Children's Sleep Habit Questionnaire (CSHQ) to 32 children who met the inclusion and exclusion criteria. The questionnaires were completed before and after the foot reflexology massage intervention.The results of the univariate analysis showed that the majority of respondents (50%) did not have good sleep quality before the massage. The majority of respondents (50%) had good sleep quality after the massage. There is an effect of foot reflexology massage on sleep quality in children in the pediatric ward of RSUD Siti Aisyah Lubuklinggau, with a ρ-value of 0.000 (< α = 0.05). Therefore, H1 is accepted and H0 is rejected.Foot reflexology massage therapy can be used as an alternative therapy to improve sleep quality in children aged 6-10 years old after hospitalization and to provide knowledge that foot reflexology massage is necessary to support the healing process.